Arquivos universitários: o acesso e a difusão dos acervos e serviços dos setores de arquivo das IFEs da região Sul do Brasil - Lima, Eliseu dos Santos (2016)
This research verifies how the sectors responsible for managing the information in the Federal Higher Education Institutions (IFES), here referred to university archives, are using the web as dissemination of their collections, its structures, and activities. This study aims to investigate the use of sites in the dissemination of archival services and distribution platforms and access in the disclosure of documentary heritage guarded by archives sectors of IFES in southern Brazil. The justification for the investigation comes from the fact of showing how the university archives can use the internet as a way of disseminating its collections and its services, dynamising the access to the information. In this sense, a theoretical reference was raised to support the objectives of the study, dealing with cultural and documentary heritage, information, dissemination of archival collections and services, access platforms, distribution and description of records, internet, website and website archival institutions, university and university archives. The contextualization of the IFES survey located in the setting of national policy archives, presenting the National System of Archives, the National Archives, the National Council on Archives and Records Management System Archives Federal Public Administration. It is a kind of applied research, descriptive, qualitative / quantitative, which was characterized as a case study. Data collection was carried out through form, which collected data from the information available on the pages of the archives sectors on the internet and questions directed to IFES submitted in the Electronic System of the Citizen Information Service (e-SIC), the Executive Branch Federal. With this study it was found that: the creation of archives sectors is a reality in Federal Universities as most have structured archives services, while the Federal Institutes, mostly not yet constituted such plants; the use of websites by the IFES archives sector is still incipient because no Federal Institute using this tool, and the Universities few archives sectors provide web pages taking part in the Conarq's recommendations for building websites; the use of access platforms, dissemination and recordkeeping description is still not a reality in IFES, for no Federal Institute makes use of this tool and few Federal Universities have adopted the ICA-AtoM, a platform that provides access to and dissemination of heritage documentary. From the results of the survey were prepared Recommendations for the construction or restructuring Archives Sectors websites of Federal Institutions of Higher Education, which contains guidelines for IFES who need to create or adapt their websites.